2012
DOI: 10.1080/08941920.2011.569855
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trust in Community Wildland Fire Protection Planning

Abstract: Growing accumulations of fuel, changing climates, and residential development in forested landscapes have accelerated the risk of wildland fire, particularly in the western United States. The magnifying level of risk of fire in the urban-wildland interface requires multiple actors implementing coordinated fuel management, fire suppression, and community protection activities. The successful implementation of such actions is built upon trusting relationships in fire protection planning process. Trust is fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 27 publications
(26 reference statements)
1
38
1
Order By: Relevance
“…Specifically, distrust between stakeholders can lead to stalemates in planning, lawsuits that hold up management actions, noncompliance with regulations, public protests, and even violence (Cvetkovich and Winter 2003, Vaske et al 2007, Stern 2008a,b, 2010, Lachapelle and McCool 2012. The inability of groups to trust each other can severely undermine the potential for learning and experimentation, leading to suboptimal outcomes for all parties involved and for natural resources .…”
Section: Institutional Resiliencementioning
confidence: 99%
“…Specifically, distrust between stakeholders can lead to stalemates in planning, lawsuits that hold up management actions, noncompliance with regulations, public protests, and even violence (Cvetkovich and Winter 2003, Vaske et al 2007, Stern 2008a,b, 2010, Lachapelle and McCool 2012. The inability of groups to trust each other can severely undermine the potential for learning and experimentation, leading to suboptimal outcomes for all parties involved and for natural resources .…”
Section: Institutional Resiliencementioning
confidence: 99%
“…Past research has also established the importance of social capital, i.e., relations of trust and reciprocity, in improving wildfire planning and management (Bihari andRyan 2012, Lachapelle andMcCool 2012). For example, the Fire Learning Network, led by The Nature Conservancy, an environmental nongovernmental organization (NGO), and composed of fire managers from diverse agencies and landscapes, utilizes collaboration across organizations and jurisdictions to result in new guiding narratives for institutional reform and the diffusion of fire management innovations across otherwiseisolated communities of practice .…”
Section: Linking Within and Across Scalesmentioning
confidence: 99%
“…For example, in a study of national parks in the United States and Ecuador, trust in protected areas authorities proved to be a key predictor of compliance with park regulations, with distrust predicting noncompliance (Stern 2008a). Trust held by community members for natural resource agencies has also been shown to increase public approval of management decisions and minimize resistance to planning efforts (Cvetkovich and Winter 2003;Lachapelle and McCool 2012;Vaske et al 2007). Studies from multiple disciplines have identified trust as an important driver of collaboration, conflict resolution, and enhanced group performance in various contexts (Fulmer and Gelfand 2012;Ostrom 2003).…”
mentioning
confidence: 99%